ANALISIS PERAN KUALITAS BAHAN BAKU, RESPONSIVITAS PEMASOK DAN BERBAGI INFORMASI TERHADAP KINERJA OPERASI USAHA RUMAH MAKAN - Mega Pertiwi; dede Siregar; Intan Diane Binangkit (JURNAL MANAJEMEN DAKWAH, 2023)
Operational performance is essential in determining the success of companies in every sector since its position reflects the company's performance. In ensuring better performance, firms compete to absorb the suitable strategy such as choosing suppliers, hoping that performance can be improved. This study aims to analyze how three supplier selection factors, namely raw materials quality, responsiveness, and information sharing, have an impact on the operational performance of restaurants in Pekanbaru. To achieve the goals, a survey was conducted by distributing questionnaires to owners and managers. Data obtained from the questionnaire is analyzed using linear regression. Results show that raw material quality has a positive significant impact on operational performance. Supplier responsiveness also has a positive and significant impact on operational performance. It is also found an appropriate information sharing between suppliers and restaurants has a significant positive impact on operational performance.